2019
DOI: 10.1186/s12866-019-1673-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the effects of different feeding habits and diets on intestinal microbiota in Acipenser baeri Brandt and Huso huso

Abstract: BackgroundSiberian sturgeon (Acipenser baeri Brandt) and Beluga sturgeon (Huso huso) are two important commercial fish in China, and the feeding habits of them are very different. Diets and feeding habits are two significant factors to affect the gastrointestinal microbiota in fish. The intestinal microbiota has been reported to play a key role in nutrition and immunity. However, it is rarely reported about the relationship between the intestinal microbiota and feeding habits/diets on different Acipenseridae f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 62 publications
2
23
1
Order By: Relevance
“…The intestinal microbiota plays an important role in fish health by providing vital nutrients and stimulating the innate immune response, the balance of bacteria communities in the intestine for the natural resistance of fish (Abdelhamed et al, 2019). The alpha diversity is a reflection of richness and diversity indices of the bacterial communities, including indexes of Chao1, ACE, Shannon and Simpson (Xu et al, 2019). In the present study, PACs group showed higher values of Chao1 and ACE index compared with control group, demonstrated that dietary PACs could improve the richness of the intestinal microbiota of American eel.…”
Section: Discussionsupporting
confidence: 54%
“…The intestinal microbiota plays an important role in fish health by providing vital nutrients and stimulating the innate immune response, the balance of bacteria communities in the intestine for the natural resistance of fish (Abdelhamed et al, 2019). The alpha diversity is a reflection of richness and diversity indices of the bacterial communities, including indexes of Chao1, ACE, Shannon and Simpson (Xu et al, 2019). In the present study, PACs group showed higher values of Chao1 and ACE index compared with control group, demonstrated that dietary PACs could improve the richness of the intestinal microbiota of American eel.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, a common phylum in marine fish is Proteobacteria [ 69 ], standing out for participating in various biogeochemical processes (carbon, nitrogen, and sulfur cycling) in aquatic ecosystems [ 70 ]. Here, this phylum is present in the intestinal microbiota of fish receiving all diets and is mostly represented by genera including Pseudomonas , Stenotrophomonas , Luteibacter , and Vibrio .…”
Section: Discussionmentioning
confidence: 99%
“…The well-known complex intestinal tract is colonized by a large and diverse type of microbial microbiota [10]. This community produces extensive amount of metabolic products in intestine, which interact intimately with host cells to maintain physiological processes and functions i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This community produces extensive amount of metabolic products in intestine, which interact intimately with host cells to maintain physiological processes and functions i.e. nutrition absorption, host metabolism, and immunity [10][11][12]. Mainly, microbiota bene ts the host through intestinal epithelium and by producing bene cial metabolites, that helps in food digestion and also against the pathogenic invasion.…”
Section: Introductionmentioning
confidence: 99%